LINKING MIDDLE SCHOOL STUDENTS TO THE KNOWLEDGE OF INVASIVE EXOTIC SPECIES OF PLANT ORIGIN IN CUBA - Expósito-Pérez, Mairely (2021)
The research carried out consisted of the design, elaboration and proposal of a system of workshops with the objective of contributing to the knowledge about Invasive Exotic Species (IES) of plants, by school children of the Rural Basic Secondary School "Wilmina Vizcaino Sarduy" located in the town of Manajanabo, in the municipality of Santa Clara, province of Villa Clara, in the Republic of Cuba. For the development of the research, different methods of information gathering and processing were used in their dialectic interrelation, which allowed verification of the existing deficiencies regarding the knowledge of plant species considered to be IES and their undesirable effects on the vulnerable Cuban ecosystems, considering that there are 8 species of invasive exotic plants in the area. The system of workshops was proposed from the school's educational project. The proposal was evaluated to be pertinent by the expert criterion method. Its validation made it possible to verify the progress made by the schoolchildren once the workshops were concluded. It is concluded that these activities contribute to the knowledge of IES of plants, development of skills, strengthening of values related to environmental education, sustainable development and confronting climate change.